Dataset of trace elements to calcium ratios of Arctica islandica shells - Ballesta-Artero, Irene (Netherlands Institute for Sea Research and Utrecht University, 2018)
Laboratory controlled experiment of trace elements to calcium ratios of Arctica islandica shells at different temperatures and food conditions.